Program Tasyji’ al-Lugah dalam Pembelajaran Bahasa Arab dan Inggris di SDMT Ponorogo - Ummul Fadhilah Arrobiah; Wahyu Hanafi Putra; Kunti Nadiyah Salma (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to: (1) Describe the planning of the tasyji'ul lughoh program for grade 6 students at SDMT Ponorogo. (2) Knowing the material presented in the tasyji'ul lughoh program for grade 6 students at SDMT Ponorogo. (3) Explain the methods and media used in the tasyji'ul lughoh program for grade 6 students at SDMT Ponorogo. (4) Describe the form of evaluation in the tasyji'ul lughoh program for grade 6 students at SDMT Ponorogo. This type of research is field research with descriptive qualitative approach. The research location was at the Integrated Muhammadiyah Elementary School (SDMT) Ponorogo. Data collection techniques using observation, interviews, and documentation. To analyze the data using data reduction triangulation techniques, data presentation, and drawing conclusions or data verification. This study's results indicate that the program's implementation is excellent because it can foster students' love for learning Arabic and English. Students' ability to master learning and speaking skills using Arabic & English is in good condition. Language support activities provided by Asatidz/Ustadzat can support students in getting Arabic and English. Factors supporting the activity were figures from the SDMT leadership, the quality of asatidz/ustadzat, TPMPS and ISMUBA administrators, a supportive school environment, and student enthusiasm